Fe2O3–TiO2 Nano‐heterostructure Photoanodes for Highly Efficient Solar Water Oxidation. Issue 17 (3rd September 2015) - Barreca, Davide; Carraro, Giorgio; Gasparotto, Alberto; Maccato, Chiara; Warwick, Michael E. A.; Kaunisto, Kimmo; Sada, Cinzia; Turner, Stuart; Gönüllü, Yakup; Ruoko, Tero‐Petri; Borgese, Laura; Bontempi, Elza; et al.
Abstract : Harnessing solar energy for the production of clean hydrogen by photoelectrochemical water splitting represents a very attractive, but challenging approach for sustainable energy generation. In this regard, the fabrication of Fe2 O3 –TiO2 photoanodes is reported, showing attractive performances [≈2.0 mA cm −2 at 1.23 V vs. the reversible hydrogen electrode in 1 M NaOH] under simulated one‐sun illumination. This goal, corresponding to a tenfold photoactivity enhancement with respect to bare Fe2 O3, is achieved by atomic layer deposition of TiO2 over hematite (α‐Fe2 O3 ) nanostructures fabricated by plasma enhanced‐chemical vapor deposition and final annealing at 650 °C. The adopted approach enables an intimate Fe2 O3 –TiO2 coupling, resulting in an electronic interplay at the Fe2 O3 /TiO2 interface. The reasons for the photocurrent enhancement determined by TiO2 overlayers with increasing thickness are unraveled by a detailed chemico‐physical investigation, as well as by the study of photogenerated charge carrier dynamics. Transient absorption spectroscopy shows that the increased photoelectrochemical response of heterostructured photoanodes compared to bare hematite is due to an enhanced separation of photogenerated charge carriers and more favorable hole dynamics for water oxidation. The stable responses obtained even in simulated seawater provides a feasible route in view of the eventual large‐scale generation of renewable energy. Abstract : The performances of ≈2.0 mA cm −2 photocurrent at 1.23 V vs. RHE under simulated solar irradiation, along with the system activity even in seawater, pave the way to the sustainable generation of renewable energy starting from abundant natural resources.